The effect of green finance and unemployment rate on carbon emissions in china - Cui, Yiniu; Wang, Gangyi; Irfan, Muhammad; Wu, Desheng; Cao, Jianhong (Frontiers in Environmental Science, 2022)
China's economy has developed rapidly since the reform and opening up, but under the long-term traditional extensive development model, energy consumption is excessive and carbon emissions rank first in the world. Therefore, how to reduce carbon emissions is a current hot issue in China. Although many scholars have found that green finance is the basic driving force to promote carbon emission reduction, its role path is diverse, and it still needs to be explored in width and depth. Especially in the green transformation stage of the economy, the potential unemployment risk is also a matter of concern. This paper selects 30 provincial panel data of the Chinese mainland for 2004-2019 years to investigate the impact of green finance on carbon emissions from the perspective of unemployment using ordinary least square (OLS), generalized method of moments (GMM), and mediating effect models. The findings show that: (1) Green finance has a significant inhibitory impact on carbon emissions; (2) Green finance has significantly reduced unemployment rate; (3) Carbon emissions increase significantly with increasing unemployment rate; (4) There are regional heterogeneity in the effect of green finance on carbon emissions in eastern, central and western China. Green finance in the eastern and central regions significantly inhibits carbon emissions, especially in the central region, while insignificantly in the western region. (5) According to the OLS and mediating effect regression results, economic growth and environmental regulation play a significant positive role in promoting carbon emissions. This study has theoretical reference significance for accelerating the realization of the dual carbon goal and alleviating phased unemployment.